Determining Factors for Success Use of e-Learning in Learning Process in College - Mohammad Alfian; Hikmatul Maulidah (Politeknik Negeri Madiun, 2021)
This research was conducted to determine the use of e-Learning that was conducted by students in College. The main purpose of this research was to find out the factors that make up e-learning successfully used in teaching learning in College. The variables in this study were e-Learning Quality, Information Quality, Use of e-Learning, User Satisfaction and Success of e-Learning. The respondents in this study were active students who used e-learning in their teaching and learning process. The number of respondents in this study were 206 respondents. The respondents in this study were students who use e-learning in teaching and learning processes in College around Pekalongan residency. The data processing in this study used the SmartPLS 3.0 tool. The results of this study showed that the quality of e-learning affects user’s satisfaction and use of e-learning. Furthermore, the quality of information generated from e-Learning only affected user’s satisfaction but it did not affect the use of e-learning. The successful use of e-learning was effect by user’s satisfaction and use of e-learning.